Policy analysis in Romania regarding the transition to an industry with low carbon emissions - Szabo, Denisa; Blagu, Diana; Dragomir, Mihai (Technium Social Sciences Journal, 2021)
This paper aims to perform a policy analysis and determine improve pathways for the Romanian industrial field in terms of the low carbon industry transition. In order to obtain the expected results, the Hoshin Kanri methodology has been applied upon the existing strategic framework in order to determine possible concrete actions to be undertaken by the companies. The Romanian manufacturing industry must become more competitive and at the same time align with the goals of carbon neutrality assumed at European and national level. Since the programmatic documents are rather general, the authors believe that firms could benefit from more direct support and assistance, in a collaboration between the public and private sectors.